2018
DOI: 10.5588/pha.18.0028
|View full text |Cite
|
Sign up to set email alerts
|

Has the utilisation of Xpert® MTB/RIF in Manicaland Province, Zimbabwe, improved with new guidance on whom to test?

Abstract: Z imbabwe has one of the world's highest tuberculosis (TB) burdens, with an estimated TB incidence of 208 cases per 100 000 population and an associated TB-HIV (human immunodeficiency virus) coinfection rate of 67% in 2016. 1 For many years, the diagnosis of pulmonary TB has relied on sputum smear microscopy, although the test has poor sensitivity and does not detect drug-resistant TB. 2 The introduction of the Xpert ® MTB/RIF assay (Cepheid Inc, Sunnyvale, CA, USA) is a game changer in this regard: Xpert is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 10 publications
3
10
0
Order By: Relevance
“…Our study found a significant increase (11%) in bacteriological confirmation when Xpert was offered to all presumptive patients. This was similar to studies in other countries and regions [12,[27][28][29], although the proportion varied, ranging from 5% in Zimbabwe [29] to 59% in Brazil [27]. We also noted the relatively low sensitivity of Xpert in this study (88% for smear-positive, culture-positive patients; 64% for smear-negative, culture-positive patients) compared to the findings in a Cochrane review (98% for smearpositive, culture-positive patients; 67% for smear-negative, culture-positive patients) [30].…”
Section: Discussionsupporting
confidence: 91%
“…Our study found a significant increase (11%) in bacteriological confirmation when Xpert was offered to all presumptive patients. This was similar to studies in other countries and regions [12,[27][28][29], although the proportion varied, ranging from 5% in Zimbabwe [29] to 59% in Brazil [27]. We also noted the relatively low sensitivity of Xpert in this study (88% for smear-positive, culture-positive patients; 64% for smear-negative, culture-positive patients) compared to the findings in a Cochrane review (98% for smearpositive, culture-positive patients; 67% for smear-negative, culture-positive patients) [30].…”
Section: Discussionsupporting
confidence: 91%
“…Inadequate coverage of diagnostic and treatment facilities, as well as the poor availability of health products and other operational challenges is well documented in studies from SSA [ 56 58 , 62 , 65 68 , 70 79 ]. Our study agrees with these findings.…”
Section: Discussionmentioning
confidence: 99%
“…47 ► Enable same day treatment initiation after Xpert 37 ► Two sputum specimen at baseline 27 ► Increase capacity and quality of inpatient and community-based care 51 ► Ensuring continuous supply of health products. 49 ► Expanded and timely access to treatment regimens, facilities and strategies. 8 21 23 Affordability:…”
Section: Recommendationsmentioning
confidence: 99%